2022
DOI: 10.1111/1911-3846.12775
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Managerial Discretion in Revenue Recognition: A Reexamination*

Abstract: Although the FASB and IASB conceptual frameworks identify relevance and faithful representation as the fundamental qualitative characteristics of useful information, prior research suggests that revenue recognition accounting standards that restrict managerial discretion resulted in improved faithful representation but reduced relevance. We use the adoption of Accounting Standards Update (ASU) 2009‐13 and ASU 2009‐14 to examine the effects of increased managerial discretion to accelerate revenue recognition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 84 publications
0
1
0
1
Order By: Relevance
“…Hartlieb y Loy (2022) estiman que, al considerar la suavización de ingresos como la estrategia de administración de ganancias, las estrategias de ajuste de recursos subyacentes al comportamiento de los costos también podrían tener un impacto en las opciones de información de la contabilidad administrativa en términos financieros a largo plazo. Por su parte, Myers et al (2022) destacan la relevancia cualitativa de la información contable para efectos administrativos y un mejor manejo de la discrecionalidad en el control de ingresos y ganancias. Revelan que una mayor discreción da como resultado un aumento en la relevancia de los ingresos reportados, sin reducir la representación fiel, por cuestiones fiscales, legales o sociales.…”
Section: Discussionunclassified
“…Hartlieb y Loy (2022) estiman que, al considerar la suavización de ingresos como la estrategia de administración de ganancias, las estrategias de ajuste de recursos subyacentes al comportamiento de los costos también podrían tener un impacto en las opciones de información de la contabilidad administrativa en términos financieros a largo plazo. Por su parte, Myers et al (2022) destacan la relevancia cualitativa de la información contable para efectos administrativos y un mejor manejo de la discrecionalidad en el control de ingresos y ganancias. Revelan que una mayor discreción da como resultado un aumento en la relevancia de los ingresos reportados, sin reducir la representación fiel, por cuestiones fiscales, legales o sociales.…”
Section: Discussionunclassified
“…Magerakis argues that the positive relationship between CEO competence and firm cash holdings is weakened by firm-level managerial discretion, that is, managerial discretion may affect the amount of a firm's cash holdings [ 33 ]. Myers et al argue that increased discretion increases the relevance of reported income but does not reduce faithful representation [ 34 ]. Chen et al examine how managerial discretionary ‘chokehold’ affects firm investment efficiency (IE) [ 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%